Artificial Intelligence and Academic Ethics in The Era of Merdeka Belajar : How Are Students' Responses? - Sariyasa Sariyasa; Ketut Ayu Lola Monika (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This study aims to analyze students' responses to using Artificial Intelligence (AI) and academic ethics in the era of independent learning. This research uses a qualitative approach with a case study method. Participants in this study were selected by purposive sampling, namely Postgraduate Students in Basic Education, Ganesha University of Education, Singaraja Campus. Data collection techniques using questionnaires and documentation. The data analysis technique was carried out descriptively by analyzing the average percentage of the questionnaire items. The results of this study showed that 56.67% of students said that AI was responsive, 89.44% of students said that AI was practical and efficient, 78.89% of students said it was interactive, 94.17% of students said it was useful in courses and design, and 94.67% said it was useful in individual learning processes. Academic ethics must also be continuously implemented when using AI in learning activities, making scientific writing assignments, making learning media with integrity, honesty, paraphrasing, and citing sources. To conclude, recommendations for higher education students should use this AI wisely.